Smart Plant Pot Robot with IoT Integration for Indoor Ornamental Plants Care - Halawa, Hestin Nalurita; Aisuwarya, Ratna (Universitas Andalas, 2023)
Caring for indoor ornamental plants is a challenge for the owner. They require special attention and treatment from the owner to grow well and beautifully. The most important and common thing that must be considered is choosing the type of plant that can adjust to the atmosphere and conditions in the room. Some indicators that determine the typical environmental conditions of potted ornamental plants are air temperature and humidity, light, and soil moisture. The smart plant pot robot is designed to provide smart care for indoor ornamental plants by incorporating a line follower mechanism. Equipped with functionalities like plant watering and environmental monitoring (including light, temperature, and humidity levels), this robot offers comprehensive plant care. Users can conveniently monitor these parameters via a smartphone using the Blynk application. In its design, the robot integrates various components such as temperature and humidity sensors, light intensity sensors, photodiode sensors, ultrasonic sensors, voltage sensors, Arduino Uno, relays, water pumps, RTC, ESP8266, DC motors, and motor drivers. The primary goal is to create a system capable of monitoring plant conditions and providing watering assistance, utilizing line tracking for transporting potted plants to sunlight exposure spots. This system aims to offer practical benefits to the community, especially in optimizing indoor ornamental plant care. The test results of this system, utilizing Arduino Uno as the microcontroller and ESP8266 for WiFi communication with the Blynk application, along with various sensors as input devices, demonstrate a remarkable 100% success rate. Notably, this accuracy is based on functional testing, encompassing everything from the robot's path detection to its connectivity with the Blynk application.